Perbandingan Konsep Keuangan pada Bank Syariah dan Bank Konvensional - Miftahuddin Miftahuddin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This paper attempts to review the comparison of the Islamic and Conventional Banks in Indonesia. There are 11 sub-topics which discuss on the concepts and matters related to both type of Banks. This include the elaboration about principles, products, institutions, time value of money, and interest versus profit-sharing. For each principles, it derived from the Al-Qur’an and Hadith. All explanations are the important points associated with the Islamic banks systems. With the examples and real simulation in calculations which presented in this article, each products can be understood comprehensively by the readers. This Islamic banking concept reveals the values, norms, and ethical aspects such as justice, fairness, trusworthy for the creditors and debitors that also bring goodness or maslahah to the society. It is expected that Islamic banks could deliver excellent services and compete internationally. With all the supports from stakeholders, the development and growth of Islamic banks is achievable.